INTERPRESTASI BESAR DAN ARAH TEGANGAN PLAT BERDASARKAN REGANGAN YANG DIUKUR - Suarnita, I. Wayan (MEKTEK, 2006)
To know the structure response while loading, object that should be measure ice: (a) strain, (b) deflection ordisplacement (c) reaction on the restrain. By using the value of strain, we can define a moment of majorstress of the points. which are observed. Strains that are happened on structure/model can be measured byusing strain gage with rectangular rosette, type in any three directions (ï¥a, ï¥b, ï¥ c). If the three directionsstrain on that point can be known